Cancer Therapy (Journal of Pharmaceutical Negative Results, 2023)
Cancer is a threat to humanity in this era. The new cases are sharply increasing. The cancer death also a major problem of the recent time. In this review the various treatment options available are described. The cancer types also explained. The WHO data of various new cases of cancer are depicted in the form of graph. The alternate therapies are reviewed .These alternate therapies are a hope now for the future cancer therapy. The future prospects of cancer therapy also explained.